Pemberdayaan Oleh Lentera Anak Bali Terhadap Tukang Suwun Anak di Pasar Badung Denpasar Bali - Sunantri, Diah Alit; Tamim, Imron Hadi; Astika, Ketut Sudhana (JURNAL ILMIAH SOSIOLOGI (SOROT), 2015)
ABSTRACT Parents inability toward environment condition in their place of origin made them allowed the children to work as tukang suwun in Badung Market. This condition makes Lentera Anak Bali Foundation empowering the children who work as tukang suwun. The aim of this research is to describe the process, understanding and analyze the empowerment impact of children as tukang suwun. Empowerment process is being analyzed with empowerment theory by Parsons. Qualitative method with descriptive approach is used in this research. The result of research shows that empowerment of children as tukang suwun conducted by using mezzo approach of Parsons theory. The empowerment of mezzo approach is utilized to the group of children as tukang suwun by joint program with SKB (Sanggar Kegiatan Belajar) as government institution who educate functional literacy and entrepreneur literacy. The education and training are used as a strategy of empowerment by Lentera Anak Bali with SKB. The type of education and traning given is informal education and skill traning. The empowerment impact has seen from several changes of the children tukang suwun. Those changes can be seen by physical condition (such as cleanness and healthiness), behavioral (attitude in language used, politeness is increasing than before) although SKB had incharge financially however, the capability of children as tukang suwun unseen in their live skills. Keywords: Children as Tukang Suwun, Empowerment, Lentera Anak Bali Foundation (LAB)